Futures contracts as a means of hedging market risks - Andrés Jerónimo Arenas-Falótico; Eliza Scudiero (AiBi Revista de Investigación, Administración e Ingeniería, 2023)
This academic article examines derivative instruments, their role in financial markets, and the associated risks. Derivatives, such as options, forward contracts, and futures, have gained increasing popularity due to their potential for hedging, market efficiency, and investment opportunities. The article discusses the reasons behind the growth of derivative usage, including economies of scale and the interdependence between futures, spot, and options markets. Additionally, it emphasizes the importance of derivatives in investment decisions, risk reduction, and speculation for companies and investors. The concept of derivatives is defined, highlighting their dependence on the value of underlying assets. The article further explores different types of risks, including systematic and unsystematic risks, and emphasizes the need for risk management strategies in derivatives trading. It also delves into futures contracts, explaining their historical development and the standardized elements they encompass. The roles of different market participants, such as hedgers, speculators, and arbitrageurs, are examined, along with the crucial function of clearing houses in facilitating derivatives transactions. The article concludes by discussing price calculation methods for futures contracts, considering factors such as storage costs, interest rates, and convenience yields. The research methodology involves a theoretical analysis of derivative instruments, their markets, and risks, supplemented by practical examples. Overall, this article provides valuable insights into the theoretical framework surrounding derivatives, enhancing our understanding of their significance in modern financial systems.